2015
DOI: 10.1001/jamaoncol.2015.2756
|View full text |Cite
|
Sign up to set email alerts
|

Role of Local Radiation Therapy in Cancer Immunotherapy

Abstract: The recent success of cancer immunotherapy has demonstrated the power of the immune system to clear tumors, generating renewed enthusiasm for identifying ways to induce antitumor immune responses in patients. Natural antitumor immune responses are detectable in a fraction of patients across multiple malignant neoplasms and can be reactivated by targeting rate-limiting immunosuppressive mechanisms. In most patients, however, interventions to induce a de novo antitumor immune response are necessary. We review gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
412
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 596 publications
(438 citation statements)
references
References 73 publications
6
412
2
5
Order By: Relevance
“…The APCs activate cytotoxic T cells, which in turn activate PD-L1 on the tumor cells, so inhibitors of immune checkpoint molecules are effective in tumors with a high mutation burden but not in those with driver mutations, such as EGFR and ALK. Our results may also support the notion of combining anti-PD-1 therapy with other cytotoxic therapies, such as alkylating agents and irradiation (20), which cause DNA double-strand breaks, possibly resulting in the expression of PD-L1 on the tumor cell surface. Recent studies have shown that the STING pathway is essential to the innate immune response against tumors.…”
Section: Discussionsupporting
confidence: 82%
“…The APCs activate cytotoxic T cells, which in turn activate PD-L1 on the tumor cells, so inhibitors of immune checkpoint molecules are effective in tumors with a high mutation burden but not in those with driver mutations, such as EGFR and ALK. Our results may also support the notion of combining anti-PD-1 therapy with other cytotoxic therapies, such as alkylating agents and irradiation (20), which cause DNA double-strand breaks, possibly resulting in the expression of PD-L1 on the tumor cell surface. Recent studies have shown that the STING pathway is essential to the innate immune response against tumors.…”
Section: Discussionsupporting
confidence: 82%
“…Following double-stranded breaks in DNA, the RAD50/NBS/MRE11 complex rapidly translocates to the sites of the breakage, forming aggregated nuclear foci until the break is repaired, for example, IRIF (18,20,23,25). Thus, RAD50 can be used as a specific identifier of cells that have been exposed to high levels of radiation, acting as a biological tag of cells from patients that have been directly exposed to radiation targeted to a tumor mass (18)(19)(20)(21)(22)(23)(24)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…The recent successes of several immune check point inhibitor clinical trials in various malignancies have demonstrated wide applicability and enormous therapeutic potential of immunomodulation and have galvanized keen interest in this field (6)(7)(8)(9)(10). An ambitious goal of combining radiotherapy and immunotherapy in the clinic would be long term remission for cancer patients with metastatic disease, perhaps through an approach analogous to delivering an in-situ anti-tumor vaccine (11)(12)(13).…”
mentioning
confidence: 99%